A Big Role for microRNAs in Gestational Diabetes Mellitus - Masete, Matladi; Dias, Stephanie; Malaza, Nompumelelo; Adam, Sumaiya; Pheiffer, Carmen (Frontiers in Endocrinology, 2022)
Maternal diabetes is associated with pregnancy complications and poses a serious health risk to both mother and child. Growing evidence suggests that pregnancy complications are more frequent and severe in pregnant women with pregestational type 1 diabetes mellitus (T1DM) and type 2 diabetes mellitus (T2DM) compared to women with gestational diabetes mellitus (GDM). Elucidating the pathophysiological mechanisms that underlie the different types of maternal diabetes may lead to targeted strategies to prevent or reduce pregnancy complications. In recent years, microRNAs (miRNAs), one of the most common epigenetic mechanisms, have emerged as key players in the pathophysiology of pregnancy-related disorders including diabetes. This review aims to provide an update on the status of miRNA profiling in pregnancies complicated by maternal diabetes. Four databases, Pubmed, Web of Science, EBSCOhost, and Scopus were searched to identify studies that profiled miRNAs during maternal diabetes. A total of 1800 articles were identified, of which 53 are included in this review. All studies profiled miRNAs during GDM, with no studies on miRNA profiling during pregestational T1DM and T2DM identified. Studies on GDM were mainly focused on the potential of miRNAs to serve as predictive or diagnostic biomarkers. This review highlights the lack of miRNA profiling in pregnancies complicated by T1DM and T2DM and identifies the need for miRNA profiling in all types of maternal diabetes. Such studies could contribute to our understanding of the mechanisms that link maternal diabetes type with pregnancy complications.